Advances in therapeutic use of a drug-stimulated translational readthrough of premature termination codons - Maciej Dabrowski; Zuzanna Bukowy-Bieryllo; Ewa Zietkiewicz (BMC, 2018)
Abstract Premature termination codons (PTCs) in the coding regions of mRNA lead to the incorrect termination of translation and generation of non-functional, truncated proteins. Translational readthrough of PTCs induced by pharmaceutical compounds is a promising way of restoring functional protein expression and reducing disease symptoms, without affecting the genome or transcriptome of the patient. While in some cases proven effective, the clinical use of readthrough-inducing compounds is still associated with many risks and difficulties. This review focuses on problems directly associated with compounds used to stimulate PTC readthrough, such as their interactions with the cell and organism, their toxicity and bioavailability (cell permeability; tissue deposition etc.). Various strategies designed to overcome these problems are presented.